Can Clinicians Trust Objective Measures of Hip Muscle Strength From Portable Dynamometers? A Systematic Review With Meta-analysis and Evidence Gap Map of 107 Studies of Reliability and Criterion Validity Using the COSMIN Methodology - Waiteman, Marina C. [UNESP]; Garcia, Micah C.; Briani, Ronaldo V. [UNESP]; Norte, Grant; Glaviano, Neal R.; de Azevedo, Fábio M. [UNESP]; Bazett-Jones, David M. (Journal of Orthopaedic & Sports Physical Therapy (JOSPT), 2023)
t OBJECTIVE: To summarize the evidence on reliability and criterion validity of hip muscle strength testing using portable dynamometers. t DESIGN: Systematic review with meta-analysis. t LITERATURE SEARCH: Five databases were searched from inception to March 2023. t STUDY SELECTION CRITERIA: We included studies investigating reliability or criterion validity of hip flexor, extensor, abductor, adductor, or internal/external rotator strength testing with portable dynamometers in injury-free individuals or those with pelvic/ lower limb musculoskeletal disorders. t DATA SYNTHESIS: We performed meta-analyses for each muscle group, position, and method of fixation. We rated pooled results as sufficient (>75% of studies with correlations ≥0.70), insufficient (>75% of studies with correlations <0.70), or inconsistent (sufficient/insufficient results). We assessed the quality of evidence, created evidence gap maps, and made clinical recommendations. t RESULTS: We included a total of 107 studies (reliability 103, validity 14). The intrarater and interrater reliability for hip muscle strength testing across different positions and methods of fixation was sufficient (intraclass correlation coefficient = 0.78-0.96) with low- to high-quality evidence. Criterion validity was less investigated and mostly inconsistent (very low–to moderate-quality evidence) with a wide range of correlations (r = 0.40-0.93). t CONCLUSION: Hip muscle strength testing using portable dynamometers is reliable. The use of portable dynamometers as clinical surrogates for measuring strength using an isokinetic dynamometer requires further investigation. Clinicians testing hip muscle strength with portable dynamometers should use external fixation seated for hip flexors, prone or supine for hip extensors, side-lying or supine for abductors and adductors, and prone and seated for internal and external rotators.
Keywords: agreement; dynamometry; force; hip muscle function; isometric strength; measurement properties